2018
DOI: 10.1002/ijc.31314
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the benefits, harms and cost‐effectiveness of potential alternatives to iFOBT testing for colorectal cancer screening in Australia

Abstract: The Australian National Bowel Cancer Screening Program (NBCSP) will fully roll-out 2-yearly screening using the immunochemical Faecal Occult Blood Testing (iFOBT) in people aged 50 to 74 years by 2020. In this study, we aimed to estimate the comparative health benefits, harms, and cost-effectiveness of screening with iFOBT, versus other potential alternative or adjunctive technologies. A comprehensive validated microsimulation model, Policy1-Bowel, was used to simulate a total of 13 screening approaches involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 40 publications
1
72
0
Order By: Relevance
“…39 A recent comparative evaluation concluded that the current NBCSP was estimated to have the most favourable cost-effectiveness and benefits-to-harms ratios when compared with alternative screening technologies. 38 The currently targeted screening age range, 50-74 years, was found to be the optimal age range for biennial iFOBT screening when compared with alternative age ranges. 34 Lowering the NBCSP starting age to 45 years was predicted to be potentially cost-effective (incremental CER: $19 126/LYS) but have a less favourable benefitto-harm balance (more than 1200 NNS per additional colorectal cancer death prevented) than screening for the currently targeted 50-74 years age group (Table 1).…”
Section: Colorectal Cancermentioning
confidence: 91%
See 1 more Smart Citation
“…39 A recent comparative evaluation concluded that the current NBCSP was estimated to have the most favourable cost-effectiveness and benefits-to-harms ratios when compared with alternative screening technologies. 38 The currently targeted screening age range, 50-74 years, was found to be the optimal age range for biennial iFOBT screening when compared with alternative age ranges. 34 Lowering the NBCSP starting age to 45 years was predicted to be potentially cost-effective (incremental CER: $19 126/LYS) but have a less favourable benefitto-harm balance (more than 1200 NNS per additional colorectal cancer death prevented) than screening for the currently targeted 50-74 years age group (Table 1).…”
Section: Colorectal Cancermentioning
confidence: 91%
“…23 Numbers provided in Table 1 show that the renewed NCSP would avert more cancer cases and deaths, requires fewer screening tests in a woman's lifetime, is less costly, and has a more favourable benefit-to-harm balance when compared with the pre-renewal NCSP. The NNS and NNT per cancer death prevented were calculated by dividing the number of people screened and number of diagnostic assessments, respectively, by the number of cancer deaths prevented per annum c The screening program participation assumed for the cost-effectiveness analyses were ~53% (2-year participation) for pre-renewal NCSP 25,37 , 86% (5-year participation) for renewed NCSP, ~55% (2-year participation) for biennial mammography screening 33 , ~40% (2-year participation) for biennial iFOBT screening 34,38 , and 95% for annual LDCT screening The estimates were calculated from outcomes predicted for a single cohort with full exposure to the biennial program. 34 The estimates would be 4619 colorectal cancers and 2719 colorectal cancer deaths prevented per annum if the average of the total number of cases and deaths prevented predicted for 2020-2040 was used 39 j Including the cost of iFOBT screening, colonoscopy (to follow up positive iFOBT result and downstream surveillance), polypectomy and colorectal cancer treatment k People who had a 30 pack-year smoking history, still smoked or had quit within 15 years prior (based on selection and implementation criteria of the National Lung Screening Trial in the US) 40 In 2018, Australia adopted a nonavalent HPV (HPV9) vaccine to replace HPV4 vaccine.…”
Section: Cervical Cancermentioning
confidence: 99%
“…A strength of this study is the use of a comprehensive and well-calibrated model [3,9] to address scenarios for program adherence, including both realistic goals in the Australian setting and high participation scenarios to assess the limits of screening. The model incorporates detailed screening, diagnosis and surveillance management pathways, observed NBCSP adherence rates, and cancer treatment costs consistent with the best available data.…”
Section: Discussionmentioning
confidence: 99%
“…Previous NBCSP evaluations, including assessments of alternative screening technologies or different target age ranges, concluded that the current NBCSP recommendations encapsulate the best option for organised CRC screening in Australia at this time, and that encouraging higher screening participation would make the program more effective whilst remaining cost-effective. [3,4,[9][10][11] The currently observed participation rate for the NBCSP (~40%) is lower than rates for the other two population-based cancer screening programs in Australia; in 2014-2016, the observed 2-yearly participation was 54-55% for BreastScreen Australia and 56-58% for the National Cervical Screening Program. [12,13] Interventions to increase screening participation through a mass-media awareness campaign have been trialed internationally,[14] and a 7-week campaign in Victoria resulted in an increase in NBCSP iFOBT kit returns to over 50%.…”
Section: Introductionmentioning
confidence: 99%
“…A recent cost-effectiveness analysis demonstrated that using iFOBT remains more cost-effective than screening using plasma and faecal DNA tests, flexible sigmoidoscopy, colonoscopy and CT colonography. 20 However, new technological and demographic developments may change the balance in the future. Technology review is important as iFOBT appears to be insensitive for detecting serrated polyps, which may be a cancer precursor in 15% of cases.…”
Section: Participation In Screeningmentioning
confidence: 99%